Optimalisasi Potensi Pemanfaatan Open Education Resources pada Pembelajaran Agama Islam - Taufik Taufik; Syafaatul Udhmah (Jurnal Bidang Pendidikan Dasar, 2021)
Open Education Resources (OER) is not just a mere expectation in the world of education but is a tangible manifestation of the existence of the development of science and technology in today's sophisticated modernization world. The ease of accessing the internet is the main support in the potential use of open learning resources for everyone. This study uses a descriptive qualitative approach with a literature study method with the aim of knowing the potential use of OER in Islamic religious Education optimally and the advantages and benefits of using it. Potential utilization of OER in Islamic religious education can optimally be done if teachers have 3 competencies and students have 2 competencies related to the use of open source learning tools. The advantages and benefits of using it are cost-effective, easy to access, flexible in place, flexible in time, as desired and can practice independent learning.